An application framework for place-based displays with mobile interaction - José, Rui (2015)
The open creation of applications is a fundamental step towards making public displays an open and creative communication medium. In this work, we describe the Displr platform for pervasive display infrastructures and particularly its application framework. The platform provides core services for managing place-based displays and an application framework that enables developers to extend the system with specific behavior. As a case study, we describe how Displr was used in the JuxtaLearn project to enable interaction with videos and quizzes presented at communal spaces of schools.